2016
DOI: 10.1080/00324728.2016.1139740
|View full text |Cite
|
Sign up to set email alerts
|

A test of the stranger-interviewer norm in the Dominican Republic

Abstract: We offer the first empirical test of the “stranger-interviewer norm,” which states that in social, demographic, and health surveys, interviewers should be strangers—not personally familiar with respondents. We use data from an experimental survey fielded in the Dominican Republic, which featured three types of interviewers: from out of town (outsiders), local but unknown to the respondent (local-stranger), and local with a prior relationship with the respondent (insiders). We were able to validate answers to u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…CBVs may also be more effective in recording neonatal and infant deaths than FPH interviewers, because they are community members, who may hear about such events through social and conversational networks [ 34 , 35 ]. FPH interviewers, on the other hand, are most commonly outsiders and strangers to whom respondents may be reluctant to disclose such private, emotional events [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…CBVs may also be more effective in recording neonatal and infant deaths than FPH interviewers, because they are community members, who may hear about such events through social and conversational networks [ 34 , 35 ]. FPH interviewers, on the other hand, are most commonly outsiders and strangers to whom respondents may be reluctant to disclose such private, emotional events [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The survey project also aims data collection at a lower cost by working with female data collectors known as resident enumerators (REs) who live in or near the sampled enumeration areas with a minimum qualification of high school completion (Hawes et al 2017;Zimmerman, OlaOlorun, and Radloff 2015). Employing local REs is one of the most unique features of PMA2020, since most large-scale surveys collect data using 'stranger-interviewers' (Sana, Stecklov, and Weinreb 2016;Weinreb 2006), whereas electronic data collection with mobile technologies using phones or tablets has increased (Paudel et al 2013). Since its inception in 2013, over 40 surveys have been conducted in 11 countries.…”
Section: Introductionmentioning
confidence: 99%
“…While the vast majority of research on this topic has focused on demographic characteristics of interviewers, there are other characteristics of interviewers that have been studied less frequently, such as the degree of familiarity between survey interviewer and respondent. The limited research on interviewer–respondent familiarity has shown that it affects survey responses 11–13…”
Section: Introductionmentioning
confidence: 99%
“…In addition, understanding of local customs may improve communication between interviewer and respondent 13. The relatively limited testing on the relationship between interviewer–respondent familiarity and survey responses suggests that data quality may improve with a greater degree of familiarity 11–13. But this relationship has seldom been examined, and research suggests that the impact of interviewer–respondent familiarity likely varies by context and over time 12 13…”
Section: Introductionmentioning
confidence: 99%